Modeling of clastogenic activity and molecular docking at the binding sites of hif-1Α-dna by 3-arylcoumarins - Collado-García, Oscar Guillermo; Salinas-Rojas, Liyoesmin; Morris-Quevedo, Humberto J.; De Winter, Hans; Molina-Pérez, Enrique (Revista Cubana de Química, 2023)
This study investigated the potential of 3-arylcoumarins to induce DNA damage and disrupt the interaction between the hypoxia-inducible factor-1α (HIF-1α) and ARNT, with the aim of hindering heterodimer formation. The clastogenic potential of 33 coumarins was assessed using ModesLab 2.0 program, and their binding affinity to HIF-1α:ARNT was modeled with MOE 2019.01 software. The results revealed that 14 of the evaluated coumarins exhibited clastogenic potential, with structural classification modeled from 10 series related to the substitution pattern. To summarize, the presence of methoxy and nitro groups in the new 3-arylcoumarins Anti-HIF-1 structure is directly linked to its ability to induce high clastogenicity. Additionally, all these compounds exhibited a full capacity for DNA binding.